2021
DOI: 10.18186/thermal.930347
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aligned Magnetic Field and Inclined Outer Velocity in Casson Fluid Flow Over a Stretching Sheet With Heat Source

Abstract: The purpose of this study was to assess the effect of the inclined outer velocity on heat and flow transportation in boundary layer Casson fluid over a stretching sheet. The flow is adopted to have non-orthogonal magnetic field with heat generation in the uniform manner on stretching surface. It has been taken that in both the directions along the xaxis, the sheet is stretched. By applying similarity transformations, the governing equations representing the heat and flow transportation are converted to ordinar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The effect of the magnetic field over nonlinearly and linearly stretching sheets has been analyzed in Chaim 6 and Ishak et al, [7][8][9] respectively under varying physical conditions. The effect of aligned magnetic field over stretching sheet has been analyzed by Devi et al 10 In these studies, it was reported that the magnetic field has a significant impact on velocity and temperature profiles of the fluid under distinct conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the magnetic field over nonlinearly and linearly stretching sheets has been analyzed in Chaim 6 and Ishak et al, [7][8][9] respectively under varying physical conditions. The effect of aligned magnetic field over stretching sheet has been analyzed by Devi et al 10 In these studies, it was reported that the magnetic field has a significant impact on velocity and temperature profiles of the fluid under distinct conditions.…”
Section: Introductionmentioning
confidence: 99%